Commercialization Strategy and Implementation Plans for the Proposed Vitual Anti-Spam System based on Feasibility Study - Zaidan, A.A.; Lakulu, M.B.; Hashim, M.; Alaa, M.; Zaidan, B.B.; Salman, O.H.; Rahmatulla, B.; Rashid, N.A. (Asian Network for Scientific Information, 2015)
The aim of this feasibility study is to find out objectively, if the proposed vitual anti-spam system (BVAS) with document processing is a viable idea in terms of technology, market considerations and finance. This feasibility study further attempts to identify the potential problems that the proposed system would face and ensure, if it is a workable and profitable business enterprise. In this study, a market strategy of the proposed vitual anti-spam will be discuss on four parts namely, market feasibility study on the use of an effective vitual anti-spam system, market feasibility analysis, formation of anti-spam company and proposed commercialization strategy, strategy justification and implementation plans. The finding from this study has shown the proposed BVAS is cheap, the anti-spam catch rate is above 98% and more importantly the false positive rate is around 0.5%. This makes BVAS to be much desired and in demand among anti-spam users. This means if BVAS is developed commercially, it can compete successfully in the open market.